1990
DOI: 10.1139/m90-071
|View full text |Cite|
|
Sign up to set email alerts
|

Variation in epitopes of the B subunit of Vibrio cholerae non-O1 and Vibrio mimicus cholera toxins

Abstract: Monoclonal antibodies reacting with the B subunit of Vibrio cholerae O1 strain 569B cholera toxin (CT-B) were used to identify unique and common epitopes of V. cholerae non-O1 and Vibrio mimicus CT-B. Vibrio cholerae non-O1 strains produced CT-B showing three monoclonal antibody reaction patterns (epitypes), which corresponded with epitypes described previously for V. cholerae O1 classical biotype CT-B (CT1), El Tor biotype CT-B (CT2), and a unique V. cholerae non-O1 CT-B (CT3), which lacked an epitope located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Thus, in effect, the present El Tor biotype strains produce CT of the classical biotype. The production of classical CT by the El Tor biotype per se is not novel and has been reported infrequently (1,11,17). In fact, U.S. Gulf Coast clones of V. cholerae O1 are El Tor strains that possess the classical CT (12).…”
mentioning
confidence: 99%
“…Thus, in effect, the present El Tor biotype strains produce CT of the classical biotype. The production of classical CT by the El Tor biotype per se is not novel and has been reported infrequently (1,11,17). In fact, U.S. Gulf Coast clones of V. cholerae O1 are El Tor strains that possess the classical CT (12).…”
mentioning
confidence: 99%
“…It has been shown that some V. mimicus strains are able to produce a heat-labile enterotoxin, functionally and immunobiologically related to the heat-labile CT (12,22), as well as other toxins and toxic substances that might contribute to its pathogenesis (5,7,8,12). Nevertheless, as in the case of V. cholerae O1, CT is probably the main factor responsible for the severity of this diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…Toxigenicity assays. V. mimicus strains were studied for heat-labile CT production by enzyme-linked immunosorbent assay (ELISA) using monoclonal antibody CT-1 (CT-B), which was kindly provided by M. L. Tamplin, University of Florida (22), and/or by the Y-1 adrenal cell assay (11). Thirty-nine isolated strains were tested for the presence of the ctxA gene by PCR using primers Col-1 (5Ј-CTCAGACGGGATTTGTTAGGCACG-3Ј, positions 197 to 220) and Col-2 (5Ј-TCTATCTCTGTAGCCCCTATTACG-3Ј, positions 475 to 498), provided by L. M. Sánchez, University of Stanford at Mexico, by the procedure described by Shirai et al (20).…”
Section: Methodsmentioning
confidence: 99%